Potensi Produk Organik Kabupaten Lumajang: Studi Komoditas Pisang Mas Kirana - Soejono, Djoko; Zahrosa, Dimas Bastara; Maharani, Ariq Dewi; Arum, Ayu Puspita; Sari, Sasmita; Amam, Amam (Universitas Galuh, 2026)
Mas Kirana banana is one of the leading commodities in Lumajang Regency which has high economic value for organic cultivation. The purpose of this study is to determine the potential mapping, implementation of agribusiness systems, economic value, and strategies for developing organic products of Mas Kirana banana commodities in Lumajang Regency. The research location was selected purposively in the Lumajang Regency area. The sampling method was purposive sampling and snowball sampling. Data collection methods used in this study include observation, interviews, and Focus Group Discussions (FGD). Data sources in this study are primary and secondary data. The results show that organic Mas Kirana banana products are very suitable for planting in the districts of Jatiroto, Kedungjajang, Klakah, Kunir, Padang, Pasirian, Randuagung, Sukodono, Tempeh, and Yosowilangun. The application of the agribusiness system in the Mas Kirana banana commodity, namely, the quality of the sapling material is not guaranteed, the materials for making fertilizers and pesticides are not guaranteed to be free from chemical contamination, cultivation, harvesting and post-harvest equipment are used for inorganic activities, limited labor both in quantity and quality (skills), access to capital sources is still limited, the market for organic banana products is limited and consumers do not differentiate between organic and inorganic products, weak management in farmer group institutions and Farmer Group Associations (Gapoktan). Mas Kirana bananas are economically obtained, namely, guaranteed better fruit quality, cost efficiency in purchasing chemical fertilizers and pesticides, and can maintain environmental balance. The priority choice of the organic Mas Kirana banana product development strategy is the importance of strengthening farmer institutions by establishing Farmer-Owned Enterprises (BUMP) in order to increase the entrepreneurial spirit, while strengthening the bargaining position in the organic product market mechanism based on science and technology.